2000
DOI: 10.1002/(sici)1097-4636(20000605)50:3<375::aid-jbm11>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Surface contact fatigue and flexural fatigue of dental restorative materials

Abstract: Antagonistic contact on a dental restoration may produce surface and subsurface stresses leading to fatigue wear as well as to bulk stressing, eventually causing catastrophic failure. It was the aim of the present work to study the outcome of two different approaches to fatigue testing of materials involving either surface contact fatigue or flexural fatigue mechanisms. A range of materials was tested, including conventional glass-ionomers, resin-modified glass-ionomers, poly-acid modified composites, and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 12 publications
0
15
1
Order By: Relevance
“…The increase in strength, as with modulus, has been attributed to chain realignment along the extension axis at low extension rates in the amorphous regions of polyethylene46 and crystallization in natural and synthetic rubbers 50. Not surprisingly, just as with the dentin fatigue studies, the results of this study are not supported by previous composite fatigue studies, which report a decreased fatigue life with increasing loading cycles and indirectly, decreased strength 19, 20. However, higher loading rates and stress levels than are associated with mastication were used in those studies.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…The increase in strength, as with modulus, has been attributed to chain realignment along the extension axis at low extension rates in the amorphous regions of polyethylene46 and crystallization in natural and synthetic rubbers 50. Not surprisingly, just as with the dentin fatigue studies, the results of this study are not supported by previous composite fatigue studies, which report a decreased fatigue life with increasing loading cycles and indirectly, decreased strength 19, 20. However, higher loading rates and stress levels than are associated with mastication were used in those studies.…”
Section: Discussioncontrasting
confidence: 89%
“…5,7 As a result, there is an extensive body of work studying fracture by static/quasistatic loading only. [10][11][12][13] The majority of cyclic loading studies that have been performed on dentin [14][15][16] and composite [17][18][19][20] are traditional fatigue studies using higher stresses and frequencies than are associated with mastication, 21 and thus do not simulate occlusal loading conditions and may not reflect clinical function failure mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the introduction of finer particles among larger ones will result in reduction of interparticle spacing and the amount of resin matrix, thus maximizing the overall properties of the material 5 . Decreased interparticle spacing caused by reduced filler size may leads to reduction in strain localization around the filler, thus reducing the fatigue failure 9,19 . The concept of multimodal fillers enables the composites to obtain high filler loading and allows a strong integration of small particles into resin matrix that can be eroded by breaking off small individual particles rather than large ones 13,19,20 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in the present study, only load to failure has been studied. One should realize that clinically, debonding occurs as a result of fatigue, where fatigue is defined as repeated loading cycles generating lower stresses than the ultimate strength of the material itself 32 …”
Section: Discussionmentioning
confidence: 99%